English

If y is mean proportional between x and z, prove that xyz (x + y + z)³ = (xy + yz + zx)³. - Mathematics

Advertisements
Advertisements

Question

If y is mean proportional between x and z, prove that xyz (x + y + z)³ = (xy + yz + zx)³.

Sum

Solution

∵ y is the mean proportional between x and z, then
y2 = xz …(i)
L.H.S. = xyz (x + y + z)3

= xzy (x + y+ z)3

= y2 y(x + y+ z)3   ...[from (i)]

= [y (x + y + z)]3

= [xy + y2 + yz]   ...[from (i)]

= (xy + xz + yz)3

= (xy + yz + zx)3

= R.H.S.

∵ L.H.S = R.H.S. hence proved.

shaalaa.com
  Is there an error in this question or solution?
Chapter 7: Ratio and Proportion - Exercise 7.2

APPEARS IN

ML Aggarwal Understanding ICSE Mathematics [English] Class 10
Chapter 7 Ratio and Proportion
Exercise 7.2 | Q 14
Share
Notifications

Englishहिंदीमराठी


      Forgot password?
Use app×